Peduli Ibu Rumah Tangga Melalui ‘Gesini” (Gerakan Deteksi Dini) Tb Anak Di Wilayah Surabaya Berbasis Kearifan Lokal - Sari, Ethyca; Aristina Halawa; Dewi Perwita Sari; Dianita Primi Hastuti (Universitas Sahid Surakarta, 2025)
Tuberculosis is an infectious disease, childhood TB occurs due to attacks by Mycobacterium Tuberculosis bacteria in the lungs and is a disease that can be cured and is not a hereditary disease. However, currently TB cases in Indonesia are still relatively high and Indonesia is ranked second after India. Children are an age that is very vulnerable to the transmission of Tuberculosis. The transmission rate and danger of transmission are high in the 0 - 6 year age group and the 7 - 14 year age group. The aim of this Community Service is to increase the knowledge and abilities of housewives through